Effect of norfloxacin therapy for acute, uncomplicated lower urinary tract infection on vaginal Candida prevalence. Issue 5 (May 2016) - Rocha, Rodrigo; Zanni, Pâmela; Souza Bonfim-Mendonça, Patrícia; Gimenes, Fabrícia; Alczuk, Silvia; Svidzinski, Terezinha; Consolaro, Márcia
Abstract Introduction and hypothesis Acute uncomplicated lower urinary tract infections (UTI) and vulvovaginal candidiasis (VVC) both occur frequently in women. Although VVC is believed to commonly occur after antibiotic therapy, few studies have demonstrated this association. Thus, the aim of the study was to estimate the prevalence of colonization byCandida spp. and VVC after norfloxacin (NOR) use for UTI and the effects on the vaginal microbiota and inflammatory process. Methods This was a prospective cohort study of women with culture-proven UTI who were treated with NOR (antibiotic group). The control group consisted of women with noninfectious diseases or in preventive care.Candida vaginal infections were monitored both clinically and mycologically at baseline and at the follow-up evaluation. Results All women showed UTI remission after NOR treatment, and no woman in either group, antibiotic and control, showed symptoms of VVC. Both groups showed similar ratios of a positiveCandida culture at baseline (6.7 % and 12.8 %, respectively) and at follow-up (3.3 % and 8.5 %, respectively) (p  = 0.2768 andp  = 0.5035, respectively). The antibiotic group showed no increased risk ofCandida colonization or VVC after NOR treatment compared with the control group [odds ratio (OR) 0.556, 95 % confidence interval (CI) 0.2407–10.05]. Conclusions NOR was effective for UTI treatment, did not increase the risk of vaginal colonization byCandida or VVC, and did not lead to major disturbances of the vaginal microbiota.